An Exploratory Analysis of the Implementation Process of the Quranic Education Program in Islamic Educational Institutions - Sumarni, Desi; Aryanti, Yosi; Arifin, Zainul; Asril, Zainal; Iskandar, M. Yakub (STIT Ahlussunnah Bukittinggi, 2024)
This research is a field study with a descriptive qualitative approach that aims to comprehensively describe the planning, implementation, and evaluation process of the tahsin program for teachers and students, as well as interpret the dynamics that occur during its implementation. The results of the study indicate that during the planning stage, the head of the school prepares teaching materials such as a tahsin guidebook, the Quran, stationery, and other supporting media such as PowerPoint and additional reference sources. Teachers prepare the guidebook, stationery, and the Quran, while students prepare the Tilawati book, stationery, and the Quran. During the implementation stage, the tahsin program for teachers is carried out once a week, while for students it is carried out four times a week using media such as the tahsin guidebook, the Quran, and the Tilawati book. Teacher evaluations are carried out continuously throughout the learning process, both at the beginning and at the end of the session. Meanwhile, student evaluations are carried out after completing each chapter of material, both verbally and in writing. The obstacles faced in the implementation of tahsin for teachers are time constraints and regular teacher absence due to other busyness, which are overcome by giving additional assignments in the form of memorizing theory or practice. Meanwhile, obstacles faced by students include low attendance rates and differences in their ability to absorb material, which are addressed by giving homework and additional time for individual tahsin.